Characteristics of hepatic fatty acid compositions in patients with nonalcoholic steatohepatitis. (10th October 2014) - Yamada, Kazutoshi; Mizukoshi, Eishiro; Sunagozaka, Hajime; Arai, Kuniaki; Yamashita, Tatsuya; Takeshita, Yumie; Misu, Hirofumi; Takamura, Toshinari; Kitamura, Seiko; Zen, Yoh; Nakanuma, Yasuni; Honda, Masao; et al.
Abstract Background & Aims Nonalcoholic fatty liver disease (NAFLD) is closely related to insulin resistance and lipid metabolism. Recent studies have suggested that the quality of fat accumulated in the liver is associated with the development of nonalcoholic steatohepatitis (NASH). In this study, we investigated the fatty acid composition in liver tissue and its association with the pathology in NAFLD patients. Methods One hundred and three patients diagnosed with NAFLD [simple steatosis (SS): 63, NASH: 40] were examined and their hepatic fatty acids were measured using gas chromatography. In addition, relationships between the composition and composition ratios of various fatty acids and patient backgrounds, laboratory test values, histology of the liver, and expression of fat metabolism‐related enzymes were investigated. Results The C16:1n7 content, the C16:1n7/C16:0 and C18:1n9/C18:0 ratios were increased and the C18:0/C16:0 ratio was decreased in the NASH group. The C18:0/C16:0 and C18:1n9/C18:0 ratios were associated with the steatosis score in liver tissue, and the C16:1n7/C16:0 ratio was associated with the lobular inflammation score. The expressions levels of genes: SCD1, ELOVL6, SREBP1c, FAS and PPARγ were enhanced in the NASH group. In multivariate analysis, the C18:0/C16:0 ratio was the most important factor that was correlated with the steatosis score. In contrast, the C16:1n7/C16:0 ratio was correlated with lobular inflammation. Conclusion The fatty acid composition in liver tissue and expression of genes related to fatty acid metabolism were different between the SS and NASH groups, suggesting that the acceleration of fatty acid metabolism is deeply involved in pathogenesis of NASH.